Exploring barriers to physical activity in patients with diabetes and hypertension : A qualitative study - Aninda Debnath; Sunanda Gupta; Jugal Kishore (Current Medicine Research and Practice)
Background: The prevalence of hypertension and diabetes in India is high and poses significant health risks. Physical activity is crucial for managing these conditions; however, engagement remains low. Aim: This study aimed to identify barriers and facilitators to physical activity (PA) amongst these patients, providing insights for effective intervention design. Materials and Methods: This qualitative study used a grounded theory approach to explore PA barriers and facilitators amongst hypertensive and diabetic patients of the Preventive Health and Screening Outdoor Patient Department, Vardhman Mahavir Medical College and Safdarjung Hospital, New Delhi. Data were collected from 20 in-depth interviews and five focus group discussions and analysed using NVivo software. Ethical approval was obtained from the institutional ethics committee. Results: The study found that barriers to PA included personal limitations (lack of time and physical pain), social and cultural obligations, environmental concerns (unsafe conditions and poor infrastructure) and inadequate health system support. Facilitators included personal motivation, family and social support, specific healthcare advice and access to safe exercise environments. Conclusion: PA is crucial for managing non-communicable diseases such as diabetes and hypertension; however, barriers such as environmental challenges, personal limitations, social influences and healthcare system inadequacies hinder participation. Facilitators included personal motivation, social support and tailored healthcare advice. Addressing these factors through targeted interventions can significantly enhance PA levels.